A guide to the morphology of bioluminescent signaling Cypridinid Ostracods from the Caribbean Sea, and a tabular key to the genera - Morin, James G.; Cohen, Anne C. (Zootaxa, 2017)
This guide is a convenient graphic description of all the salient features of the bioluminescent ostracods in the family Cypridinidae from the Caribbean Sea that are useful, and essential, for their accurate identification upon microscopic examination of dissected specimens. Over 70 species of courtship-signaling ostracods [with 22 of these formally described] have been discovered in the Caribbean, but nowhere else, and many more await discovery. The guide is also helpful for providing comparative information on the morphology of all myodocopid ostracods in the family Cypridinidae from around the globe. We also include a tabular key to males of the six known genera (3 described) of signaling cypridinid ostracods and one commonly collected non-luminescent congener.